The atlas of world hunger - Bassett, Thomas J. 1953-; Winter-Nelson, Alex E. 1963- (Univ. of Chicago Press, 2010)
Earlier this year, President Obama declared one of his top priorities to be a making sure that people are able to get enough to eat. The U.S. spends about five billion dollars on food aid & related programs each year, but still, both domestically and internationally, millions of people are hungry.
Includes bibliographical references and index
Keywords: Food supply / Maps; Atlases; Society; Food supply -- Maps; Armut; Lebensmittelversorgung; Welternährung; Hunger; Atlas